MANAJEMEN ASET TANAH MILIK PEMERINTAH KABUPATEN KUANTAN SINGINGI TAHUN 2009-2013 - Minurila "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to investigate the implementation of government-owned land asset management Kuantan Singingi in 2009-2013. And to determine the factors inhibiting land owned asset management Regency Kuantan Singingi. The theory used is the asset management theory put forward by D. Doli Siregar. The method used in this research is qualitative methods of data that is manifested in the form of an explanation that describes the shape of the state, processes, and specific events. Data collection techniques used is to use the techniques of observation, interviews, and documentation.From the data obtained findings that land owned asset management Kuantan Singingi years 2009-2013 in the planning process, Kuantan Singingi government has not increased significantly and are likely the same in every year. At its organization must put people in areas under their control for the implementation of asset management of land owned by Regency Kuantan Singingi accomplished in accordance with what has been targeted. In the implementation of government-owned land asset management Kuantan Singingi presence of the shortcomings of the management of government where in the area of good governance management should be based on performance. Note here is still difficult Singingi Kuantan District government in regulating land administration impeding the issuance of land titles and also lack of good co-operation between intansi involved in the management of land assets. Singingi Kuantan District Government has sought to manage the assets of the land but has not run well. It is caused by several factors such as: human resources, public participation and cooperation relations.Keywords: Asset Management, Land, Regency Kuantan Singingi